Puzzling over parking: Assessing the transitional parking requirement in Vancouver, British Columbia. (September 2020) - Thumm, Alex Jürgen; Perl, Anthony
Highlights: Offers a framework to consider parking requirements as a political tactic. Adds explanatory purchase to studying urban housing and mobility. Explores opportunities and challenges to parking reform. Analyses the utility of incrementalism in advancing strategic plans. Planners' assumptions were more conservative than those of elected officials. Abstract: Drawing upon Flyvbjerg's (1998) insight that planning is defined more by the political than the rational, we examine the experience of parking reform, as attempted by municipal officials, in Vancouver, British Columbia. The literature offers a broad consensus that minimum parking requirements represent a misguided and inefficient policy producing excess parking in the wrong places and reduced housing affordability. Yet minimum parking requirements remain a near-universal fixture in municipal regulations. We examine the stubborn disconnect between Vancouver's parking standards and its strategic policies. Rather than reiterating normative debates, we consider how ideas and institutions could shape officials' hesitation in reform. We reveal the compromise that ensues under planning's duality of designing credible, forward-looking strategy while managing the political constraints created by policy path dependence. We find that Vancouver's laneway housing parking requirement represents a typology that could propagate across North America: a transitional parking requirement of political compromise, which, we suggest, has the potential to produce a workable reconciliation of theory and practice.